2020
DOI: 10.1073/pnas.2000639117
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous fibrous Bouligand architecture enabling formidable fracture resistance with crack orientation insensitivity

Abstract: Bioinspired architectural design for composites with much higher fracture resistance than that of individual constituent remains a major challenge for engineers and scientists. Inspired by the survival war between the mantis shrimps and abalones, we design a discontinuous fibrous Bouligand (DFB) architecture, a combination of Bouligand and nacreous staggered structures. Systematic bending experiments for 3D-printed single-edge notched specimens with such architecture indicate that total energy dissipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 53 publications
1
84
0
3
Order By: Relevance
“…Furthermore, looking into great depths of Bouligand-like structure of a scale from an arapaima scale, numerical simulations provide an evidence in preferring a discontinuity in fibers through the layers of collagen ply to successfully increase fracture resistance and crack insensitivity which is demonstrated in Figure 15 (Wu et al, 2020).…”
Section: Figure 12 | (A)mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, looking into great depths of Bouligand-like structure of a scale from an arapaima scale, numerical simulations provide an evidence in preferring a discontinuity in fibers through the layers of collagen ply to successfully increase fracture resistance and crack insensitivity which is demonstrated in Figure 15 (Wu et al, 2020).…”
Section: Figure 12 | (A)mentioning
confidence: 98%
“…FIGURE 15 | (A) Discontinuous Bouligand fibers and (B) the numerical result of energy absorption(Wu et al, 2020).…”
mentioning
confidence: 99%
“…[ 6 ] Once the fracture occurs, twisting cracks can be developed due to the orientation distribution of mineral fibers, and the propagation of these cracks will make a significant contribution to the internal energy dissipation. [ 38–40 ] As a result, Bouligand‐like type IV structure features a remarkable energy absorption capability (Figure 5E), around 20 times that of type I and 2 times that of type II.…”
Section: Figurementioning
confidence: 99%
“…However, the heterogeneous mineral ply orientations of types III and IV, resembling the Bouigand structure in stomatopod dactyl club, [ 6 ] can efficiently bend, twist, and retard the crack propagation. [ 38–40 ]…”
Section: Figurementioning
confidence: 99%
“…Borrowing the concepts from lotus leaf and butterfly wing, we created a surface that could be used for acid/base recognition by the regulation of mechanical stress and robust transportation of water droplets. [4] Yu et al [5] It has long been demonstrated the gecko-inspired micropillar array with T-shape tips possesses the best adhesion performance of a given material. The further enhancement of the adhesion performances of T-shape micropillars can offer redundant adhesion to compensate for the inevitable improper contacts.…”
Section: Introductionmentioning
confidence: 99%